Unveiling the Realities Behind High Turnover Rate in a Three-Stars Hotel - Evianti Rachmalia; Erry Sukriah; Moh. Dede (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2024)
The existence of quality human resources is very important in the hotel industry because it has a direct impact on the services provided to guests. A high employee turnover rate can disrupt service continuity and reduce service quality. This research aims to analyze the phenomenon of worker turnover that occurs at one of the three-stars hotels in Cirebon City. This research involved eight informants as samples, based on purposive sampling techniques. The method used uses a qualitative approach with various data collect-ion techniques (triangulation) which include interviews, observation and documentation. The analysis process is classified into various categories systematically from the data that has been obtained. We con-firmed that compensation is the main factor in the high turnover rate in the hotel industry. In addition, leadership bias causes workers to feel unappreciated and choose to leave their jobs. Hotels need to pay attention to managerial aspects to achieve good corporate governance. Apart from that, the company has also not been able to discuss the rights and obligations of workers properly so that turnover does not occur in a relatively long period of time (less than 1 year).